Historis Periodesasi Perkembangan Hadis dari Masa ke Masa (Rasulullah, Sahabat, Tabi’in) - Zaenuri Zaenuri; Rahmah Zaqiyatul Munawaroh (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2021)
In the study of this discussion, the author explains the history of the development and codification of hadith from the time of the prophet, the companions and the tabi’in. things like this are certainly very important and basic before studying more broadly about hadith. The urgency of the purpose of this discussion is to study the history of hadith from time to time. This paper is expected to be an entry point in studying other hadith sciences, both in terms of their distribution, as seen from the number of narrators of their quality. The type of research method used in this research is a study of literature or literature with a descriptive qualitative approach. The result of this discussion is the development of hadith at this time, the Muslim community still does not understand hadith or write hadith. At this time the prophet always emphasized to his companions to understand the hadith and convey it to Muslims. The companies themselves are considered to have received a lot of hadith and some are also few due to factors of residence, area, age and so on. One of the greatest policies of the prophet regarding the maintenance of both of them was to command the companions to memorize and write the Qur’an, and officially appointed a revelation writer who was in charge of recording every verse of the Qur’an that was revealed under the direct instructions of the Prophet SAW. Many of the property's traditions, so the tabi’in, who are the companions’ disciples, also collect a lot of the prophet’s hadiths and even this collection is arranged in an orderly manner. The method used by the tabi’in in collecting and recording hadith is through meetings (al-talaqqi) with their friends and then the record what they get from the meeting.